2022
DOI: 10.3389/fenvs.2022.902999
|View full text |Cite
|
Sign up to set email alerts
|

Rice Straw Vermicompost Enriched With Cellulolytic Microbes Ameliorate the Negative Effect of Drought in Wheat Through Modulating the Morpho-Physiological Attributes

Abstract: Wheat growth and productivity are unfavorably pretentious by a lack of sufficient water (drought or water deficit) worldwide. Drought stress significantly affects all the morpho-physiological and biochemical characteristics and the agronomical yield of wheat. Different management approaches have been adopted to cope with the negative effects of water deficit. Soil-applied vermicompost is helpful in improving the growth and developmental processes of wheat under water deficit conditions. Therefore, a trial was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 63 publications
(72 reference statements)
0
7
0
Order By: Relevance
“…Climate change has negatively influenced the performance of rice cropping systems and seasonal variations in rainfalls has increased the chances of drought stress occurrence [48][49][50][51][52][53][54][55][56][57]. Climatic variability has posed a huge threat to worldwide food security [58].…”
Section: Discussionmentioning
confidence: 99%
“…Climate change has negatively influenced the performance of rice cropping systems and seasonal variations in rainfalls has increased the chances of drought stress occurrence [48][49][50][51][52][53][54][55][56][57]. Climatic variability has posed a huge threat to worldwide food security [58].…”
Section: Discussionmentioning
confidence: 99%
“…The chemical composition such as pH, electric conductivity, nutrient, and heavy metal concentrations of prepared vermicompost and raw material (cow-manure) quantified by following the standard protocols of Ahmad et al 2 and Aslam et al 30 is shown in Table 2 .…”
Section: Materials and Methodsmentioning
confidence: 99%
“…According to an estimate, about 788.50 million metric tons of wheat are produced worldwide each year. Genetically, wheat is categorized into two major groups: hexaploid bread wheat and tetraploid durum wheat . Bread wheat (Triticum aestivum L.) always shared a major part of the cultivated area as compared with durum wheat.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations